2009
DOI: 10.1186/1472-6750-9-41
|View full text |Cite
|
Sign up to set email alerts
|

A suite of recombinant luminescent bacterial strains for the quantification of bioavailable heavy metals and toxicity testing

Abstract: Background: Recombinant whole-cell sensors have already proven useful in the assessment of the bioavailability of environmental pollutants like heavy metals and organic compounds. In this work 19 recombinant bacterial strains representing various Gram-positive (Staphylococcus aureus and Bacillus subtilis) and Gram-negative (Escherichia coli, Pseudomonas fluorescens) bacteria were constructed to express the luminescence encoding genes luxCDABE (from Photorhabdus luminescens) as a response to bioavailable heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
142
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(146 citation statements)
references
References 73 publications
4
142
0
Order By: Relevance
“…These results indicated that, when the individual pcadCLuc, pzntRluc, or parsRluc sensors were used with mixed CdPb-As solution, Cd and Pb may mutually interfere their respective measured results and Cd may affect the measured result of As. These findings are consistent with those of previous studies, which also observed nonspecific binding of metals such as Cd and Pb to CadC; Pb, Cd, Hg, and Zn to ZntR; and As and Sb to ArsR [6,7].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These results indicated that, when the individual pcadCLuc, pzntRluc, or parsRluc sensors were used with mixed CdPb-As solution, Cd and Pb may mutually interfere their respective measured results and Cd may affect the measured result of As. These findings are consistent with those of previous studies, which also observed nonspecific binding of metals such as Cd and Pb to CadC; Pb, Cd, Hg, and Zn to ZntR; and As and Sb to ArsR [6,7].…”
Section: Resultssupporting
confidence: 83%
“…Numerous microbial whole-cell sensors have been developed to measure the soil bioavailability of toxic elements such as Cd, Pb, As, Hg, and Cr [4,5]. However, almost all the developed whole-cell sensors are nonspecific to a certain metal since the regulatory proteins, such as CadC, ZntR, and ArsR, could concurrently recognize several different metals [6,7]. Nonspecific microbial sensors that respond to multiple metals in a certain environment will tend to overestimate the bioavailability of target metals and environmental risks in a co-polluted environment.…”
Section: Introductionmentioning
confidence: 99%
“…Later, it was modified by different researchers and adapted for their specific purposes [2][3][4][5][6]. Now, the bacterial bioluminescent assay is a traditional and important biotechnological application of the bioluminescence phenomenon [7][8][9][10][11]. The tested physiological parameter here is luminescence intensity that can be easily measured instrumentally.…”
Section: Introductionmentioning
confidence: 99%
“…The bioluminescent bioreporter E. coli strains MC1061 (pmerRlux) (9), which responds to inorganic mercury, and MC1061 (pmerRBlux) (11), which responds to both inorganic and organic mercury, were used. The E. coli MC1061 (pDNlux) strain was used as a non-inducible control (11).…”
Section: Bioavailability Of Mercurymentioning
confidence: 99%